(untitled) (Bolton, Mass., 2007)
While addressing the implications of rising multilingualism in America, Learning the Language of Global Citizenship explores the link between the achievement gap and academic language proficiency, as well as civic literacy and the individuals' motivation for civic engagement. In this book, the authors show how service-learning enhances language learning, international understanding, and global civic participation skills.
Keywords: Language and languages,Service learning,Ngôn ngữ và các ngôn ngữ,Phục vụ học tập; Study and teaching,Dạy và học